TMPRSS2 gene polymorphism common in East Asians confers decreased COVID-19 susceptibility - Sekiya, Takeshi; Ogura, Yukino; Kai, Hirayasu; Kawaguchi, Atsushi; Okawa, Shino; Hirohama, Mikako; Kuroki, Takahiro; Morii, Wataru; Hara, Akira; Hiramatsu, Yuji; Hitomi, Shigemi; Kawakami, Yasushi; et al. (Frontiers in Microbiology, 2022)
COVID-19 has a wide range of clinical presentations, and the susceptibility to SARS-CoV-2 infection and the mortality rate also vary by region and ethnicity. Here, we found that rs12329760 in the TMPRSS2 gene, a missense variant common in East Asian populations, contributes to protection against SARS-CoV-2 infection. TMPRSS2 is a protease responsible for SARS-CoV-2 entry and syncytium formation. rs12329760 (c.478G>A, p. V160M) was associated with a reduced risk of moderate symptoms. The enzymatic activity of Met160-TMPRSS2 was lower than that of Val160-TMPRSS2, and thus the viral entry and the syncytium formation of SARS-CoV-2 were impaired. Collectively, these results indicate that the genetic variation in TMPRSS2, which is common in East Asians, is one of the molecular determinants of COVID-19 susceptibility.